Ferric Citrate Reduces Intravenous Iron and Erythropoiesis-Stimulating Agent Use in ESRD - Umanath, Kausik; Jalal, Diana I.; Greco, Barbara A.; Umeukeje, Ebele M.; Reisin, Efrain; Manley, John; Zeig, Steven; Negoi, Dana G.; Hiremath, Anand N.; Blumenthal, Samuel S.; Sika, Mohammed; Niecestro, Robert; et al. (Journal of the American Society of Nephrology, 2015)
Ferric citrate (FC) is a phosphate binder with shown efficacy and additional effects on iron stores and use of intravenous (iv) iron and erythropoiesis-stimulating agents (ESAs). We provide detailed analyses of changes in iron/hematologic parameters and iv iron/ESA use at time points throughout the active control period of a phase 3 international randomized clinical trial. In all, 441 subjects were randomized (292 to FC and 149 to sevelamer carbonate and/or calcium acetate [active control (AC)]) and followed for 52 weeks. Subjects on FC had increased ferritin and transferrin saturation (TSAT) levels compared with subjects on AC by week 12 (change in ferritin, 114.1±29.35 ng/ml; P<0.001; change in TSAT, 8.62%±1.57%; P<0.001). Change in TSAT plateaued at this point, whereas change in ferritin increased through week 24, remaining relatively stable thereafter. Subjects on FC needed less iv iron compared with subjects on AC over 52 weeks (median [interquartile range] dose=12.9 [1.0-28.9] versus 26.8 [13.4-47.6] mg/wk; P<0.001), and the percentage of subjects not requiring iv iron was higher with FC (P<0.001). Cumulative ESA over 52 weeks was lower with FC than AC (median [interquartile range] dose=5303 [2023-9695] versus 6954 [2664-12,375] units/wk; P=0.04). Overall, 90.3% of subjects on FC and 89.3% of subjects on AC experienced adverse events. In conclusion, treatment with FC as a phosphate binder results in increased iron parameters apparent after 12 weeks and reduces iv iron and ESA use while maintaining hemoglobin over 52 weeks, with a safety profile similar to that of available binders.